Implementasi Manajemen Strategik dalam Peningkatan Mutu Lembaga Pendidikan di Era Transformasi Digital - Fadhilah, Fadhilah; Maharni, Septi; Nurlinda, Nurlinda; Siswadi, Renalda; Salmon, Salmon; Demina, Demina (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Digital transformation requires educational institutions to develop adaptive, effective, and technology-oriented management systems. This study aims to analyse the implementation of strategic management in improving the quality of educational institutions in the era of digital transformation through a literature review. The data sources were books, scientific articles, and research publications relevant to digital education management. The results of the study show that strategic management plays an important role in aligning vision, goals, and operational actions based on data and technology. Its implementation is reflected in the development of digital education programmes, performance-based budget management, the formulation of standard operating procedures, and the strengthening of organisational structures and management information systems. The application of these strategies contributes to improving the quality of learning, governance effectiveness, institutional innovation, and educational competitiveness. However, implementation still faces challenges such as limited resources, resistance to change, and technological literacy gaps. Recommended efforts include strengthening visionary leadership, improving digital competencies, investing in technological infrastructure, and conducting continuous evaluation. This study emphasises that the integration of strategic management and digital transformation is an important foundation for creating excellent and competitive educational institutions in the 21st century.